Effects of BA and NAA on micropropagation and Stemona alkaloids production of Stemona curtisii Hook.f. - Jiraporn Palee (2018)
In vitro propagation of Stemona curtisii was explored for multiple shoot induction and root regeneration in different media. Shoot explants were cultured on solid MS media supplemented with 0, 1, 2 and 3 mg L-1benzyladenine (BA) to produce multiple shoots. This research revealed that the medium containing 2 mg L-1BA induced shoot formation at a rate of 100% with the highest number of 9.8 shoots per explant. Then, the elongated shoots were separated and cultured on MS solid and in liquid media supplemented with 0, 1, 2, 3 and 4 mg L-1naphthalene acetic acid (NAA) to induce roots. It was found that the solid medium containing 1 mg L-1NAA induced 100% root formation with the highest number of 21.5 roots per explant. For the Stemona alkaloids analysis from the in vitro roots, HPLC analysis showed the content of oxyprotostemonine 90 μg g-1DW, stemocurtisine 7 μg g-1DW and stemocurtisinol 9 μg g-1DW.